1999
DOI: 10.1034/j.1399-3054.1999.105108.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response of drought‐ and salt‐stressed tomato and turnip rape plants to foliar‐applied glycinebetaine

Abstract: The effect of foliar application of glycinebetaine (50 and 100 mM) on photosynthesis, stomatal conductance, photorespiration and transpiration in tomato cv. Bos 3155 (Lycopersicon esculentum Mill.) and summer turnip rape cv. Kulta (Brassica rapa L. ssp. oleifera) plants subjected to drought and salinity are reported. Glycinebetaine application increased net photosynthesis of stressed plants. This was mostly due to increased stomatal conductance following glycinebetaine application as there were no marked chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 25 publications
7
38
1
1
Order By: Relevance
“…However, the concerted action of disordered photochemistry and the visible damage to the photosynthetic apparatus probably led to the reduction in photosynthetic activity (Dubey 1997;Mäkela et al 1999). Our results indicate that NaCl first damaged the membranes of thylakoids (reduced number, swelling), which may finally cause the disturbance or inhibition of photochemical reactions.…”
Section: Indicated That a Littoralis Is A C 4 Poaceaementioning
confidence: 67%
See 1 more Smart Citation
“…However, the concerted action of disordered photochemistry and the visible damage to the photosynthetic apparatus probably led to the reduction in photosynthetic activity (Dubey 1997;Mäkela et al 1999). Our results indicate that NaCl first damaged the membranes of thylakoids (reduced number, swelling), which may finally cause the disturbance or inhibition of photochemical reactions.…”
Section: Indicated That a Littoralis Is A C 4 Poaceaementioning
confidence: 67%
“…Kerstiens et al (2002) showed that stomatal closure was induced by the presence of sodium ions in the apoplast surrounding the guard cells of Aster tripolium. Stomatal closure led to a reduction of photosynthesis (Seemann and Critchley 1985;Delfine et al 1998) by limiting the CO 2 entering into plant tissues (Mäkela et al 1999;Cornic 2000). The reduction of photosynthesis could potentially be due to a decrease in both stomatal conductance and mesophyll conductance.…”
Section: Discussionmentioning
confidence: 98%
“…Application of glycine betaine as a pre-sowing seed treatment was found to be ineffective in altering the gas exchange characteristics of wheat plants, although available reports are showing the positive effect of exogenously applied glycine betaine on different crops e.g., pea and turnip (Makela et al, 1998), tobacco (Ma et al, 2006) and tomato (Makela et al, 1999). Frommhold et al (1987) reported increased photosynthetic rates and decreased CO 2 compensation point in tobacco seedlings treated with thiourea.…”
Section: Physiological Parametersmentioning
confidence: 99%
“…Salinity may reduce gas exchange and chlorophyll (CHL) concentrations of wheat, and these responses are larger in salt-sensitive cultivars than in salt-resistant ones (CraftsBrandner et al, 1990;Makela et al, 1999;Lopez-Climent, 2008). Numerous studies have shown that salinity not only delays CHL biosynthesis, but it also accelerates the degradation of original CHL (Thind and Malik, 1988;Hernandez et al, 1995).…”
Section: Increased Gas Exchange and Chlorophyll Concentrationsmentioning
confidence: 99%